2003
DOI: 10.2170/jjphysiol.53.351
|View full text |Cite
|
Sign up to set email alerts
|

The Redox States of Serum and Synovial Fluid of Patients with Temporomandibular Joint Disorders

Abstract: [6] have been detected in the synovial fluid (SF) of the temporomandibular joint (TMJ). These findings may indicate that newly synthesized protein molecules tend to appear or increase in SF of the patient with TMDs. Recent studies have proposed that reactive free radicals, which were induced by mechanical stress, are responsible for the initiation of molecular events. Milam et al. [7] have hypothesized that free radicals might be produced in the intraarticular space by mechanical stresses in the TMJ, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
20
1
1
Order By: Relevance
“…According to a standard PET test, 39% of our patients were H/HA. These distribution characteristics were slightly lower than those reported in the previous studies, reporting H/HA group prevalence between 47.4 and 83% [12,13] . Our results showed that except for hypoalbuminemic, all clinical variables of high transporter (H/HA group) showed no significant difference when compared with their low transporter counterparts.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…According to a standard PET test, 39% of our patients were H/HA. These distribution characteristics were slightly lower than those reported in the previous studies, reporting H/HA group prevalence between 47.4 and 83% [12,13] . Our results showed that except for hypoalbuminemic, all clinical variables of high transporter (H/HA group) showed no significant difference when compared with their low transporter counterparts.…”
Section: Discussioncontrasting
confidence: 82%
“…HMA may be an important endogenous antioxidant within the body. Oxidized albumin forms have been shown to serve as early biomarkers for human diseases associated with oxidative stress [11,12] . Increased levels of oxidized albumin levels (high HNA level) have been reported in the serum of patients with end-stage renal disease [13,14] , though little is known about the relationship between the oxidized albumin content of the serum in patients on PD and the peritoneal membrane transport status.…”
mentioning
confidence: 99%
“…1a). We assumed that the decrease in removal of small substances (spKt/V) during the pre-OL-HDF period might be caused by the decrease in diffusion capacity by the substitution reinfusion fluid (10 L/h) [8]. We also found that serum β2-MG levels before dialysis sessions in the pre-OL-HDF period were significantly lower than those in the CHD periods (Table 2).…”
Section: Solute Removal Efficiencymentioning
confidence: 88%
“…We measured the following: blood levels of urea nitrogen (UN), creatinine, inorganic phosphorus, β2-MG, hemoglobin, albumin (Alb), total protein, and triglycerides; indices of inflammation, namely, serum C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α); and indices of oxidative stress, namely, serum 8-hydroxydeoxyguanosine (8-OHdG) and the human mercapto-Alb/human serum Alb (HMA) ratio. Serum levels of 8-OHdG (highly sensitive ELISA kit for 8-OHdG, Japan Institute for the Control of Aging, NIKKEN SEIL Co., Ltd.), IL-6 (Human IL-6 ELISA kit, Thermo Fisher Scientific Co., Ltd.), and TNF-α (human TNF-α ELISA kit, Thermo Fisher Scientific Co., Ltd.) were measured by ELISA kit, and HMA ratios were measured using a liquid chromatography mass/spectrometry system, as reported previously [8,9]. Based on the liquid chromatography mass/spectrometry system profiles of HSA obtained from these procedures, the values for each fraction were subjected to numerical curve fitting, and the fractions of HMA were calculated.…”
Section: Measurementsmentioning
confidence: 99%
“…HIGHLY OXIDATIVE STATUS OF THE AQUEOUS HUMOR IN SENILE CATARACT PATIENTS We developed a convenient high-performance liquid chromatography (HPLC) system for separating human serum albumin into HMA and HNA that uses a ShodexAsahipak GS-520H or ES-502N column (Showa Denko, Tokyo, Japan), and we have studied extensively the dynamic changes in the redox state of albumin during various pathophysiological states, such as during hepatic dysfunction, 4,5 renal dysfunction, 6-10 diabetes, 11,12 and other diseases. [13][14][15] Moreover, we have also analyzed the effects of aging 16,17 and strenuous exercise 18 on the redox state of albumin under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%